A Study on Perception Towards Inflation and Measures to Control it - Maruti Rao, N.; Naikwadi, Iftikhar Ahmed (Prabandhan: Indian Journal of Management, 2010)
Inflation is a global phenomenon and every country is facing an upsurge in inflation. Today, it is considered as an economic destructive weapon as it has hit most of the countries in the world. Worldwide, people are talking about Inflation as an economic concept as well as an economic indicator. At its most basic level, inflation is simply a rise in prices. It is a measure of price increases within a set of goods and services over a period of time. In other words, over time, as the cost of goods and services increases, the value of a currency is going to go down because you won’t be able to purchase as much with that currency as you had purchased in the past i.e. last week, last month or pervious year. It is important to note that some amount of inflation is actually desirable in the economy because of its relationship with employment and economic growth. But too much inflation is not good for the economy. Rising inflation, an economic disease has disturbed the minds of governments, economists and public as they are feeling the punch of the inflation due to rise in price of all commodities. The rise in prices has made life miserable in India and other developing and poor countries. It is a heavy tax on people at large. The industries have been hit by inflation due to rising input cost which is putting pressure on their bottom-line. The government is also losing crores of rupees due to various fiscal measures adopted by it. Inflation is also affecting the economic growth process.